Green Innovation in Jatibening: Utilizing Organic Waste to Make Compost through the Masdarling Community Service Program - Paramitra, Yuaniko; Mei R, Dhistianti; Loen, Mishelei; Saoloan S, Partogi; Rosdiana, Rosdiana; Reztrianti, Diajeng (Santoso Academy Network, 2025)
The increasing population, the growing number of products, and changes in people's consumption patterns have led to a significant rise in waste volume. This situation poses environmental challenges that require sustainable solutions. One effective way to address the increasing volume of waste is to process organic waste into compost a natural fertilizer produced by the decomposition of materials such as leaves, food scraps, and kitchen waste. Composting is environmentally friendly and beneficial for plants as it enhances soil fertility without relying on chemical substances that may harm the ecosystem. The main objective of this community service activity is to provide knowledge, guidance, and hands-on experience to residents of Jatibening, enabling them to develop awareness and practical composting skills. The program employs the Masdarling (waste-conscious community) socialization method, which focuses on education combined with direct compost production practice. This approach ensures that participants not only understand the theoretical aspects but also gain practical experience in making compost. The activity was carried out in collaboration with KKN students from Krisnadwipayana University. It involved Jatibening residents, particularly the PKK women's group, as the prominent participants in promoting sustainable waste management at the community level